ANALISIS PENGGUNAAN PANEL SURYA SEBAGAI CATU DAYA PADA PROSES INKUBASI YOGHURT - Bella Aisya Rohmawati; Moch. Dhofir; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2023)
Solar panels are basically power supplies and can be designed to supply small to large electricity needs independently or hybridly. Solar panels as a source of electrical energy supply can help sustain the energy needs of socio-economic activities, especially in the industrial sector both on a small and large scale which have not been optimally fulfilled. The PLTS design first calculates the daily load energy requirement and then compares it with the installed solar panel system that matches the daily load energy requirements for the yogurt incubation process. The calculated solar panel system is used to supply 100% of the daily load energy needs with the power capacity of solar modules, solar charge controllers and batteries must match the needs of the existing load. The calculation is done by calculating the energy requirement for a daily load with a volume of 2 liters and 2.5 liters of yogurt, which is 525.2 Wh while in practice it is 366.8 Wh. Based on the calculation of solar module power capacity, solar charge controller current capacity, and battery charge capacity, respectively, two 100 Wp solar modules of the Luminous brand, a PWM type SCC with a capacity of 30 A, and two MPower Batteries JXH 100-12G 12V with a capacity of 100 Ah. In its implementation, the battery charging time from a DoD condition of 40% using a 200 Wp solar panel is 8 hours. The battery spare time without charging is 7.2 hours with a DoD of 40%, while in a battery with a charging condition of 7.2 hours with a DoD of 20%. The PLTS system installed is able to meet the energy needs of the daily load in the incubation process of up to 10 liters of yogurt. Keywords: solar panel, power supply, yoghurt, daily energy